Ecology of the ichthyofauna in three temporarily open/closed estuaries on the Natal coast - Harrison, Trevor D (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 1994)
The ichthyofauna of three small Natal estuaries, the Mhlanga, Damba and Zotsha was sampled over a period of two years. A total of 68 kinds of fishes representing 24 families, 39 genera and 56 species were captured during this study. Forty seven kinds of fishes were recorded in the Mhlanga of which Gilchristella aestuaria,Oreochromis mossambicus, Valamugil cunnesius, Valamugil sp. and juvenile mugilids numerically dominated. In terms of biomass, O. mossambicus, V. cunnesius, Liza alata, Myxus capensis and Mugil cephalus dominated the ichthyofauna of the Mhlanga. In the Damba, 24 kinds of fishes were recorded. The most abundant fishes captured were Glossogobius callidus, M. capensis and O. mossambicus. M. capensis, M. cephalus, O. mossambicus and G. callidus dominated the fish biomass captured in the Damba. A total of 56 kinds of fishes were recorded in the Zotsha during this study. The ichthyofauna of the Zotsha was numerically dominated by juvenile mugilids, G. aestuaria, O. mossambicus, Rhabdosargus holubi, Terapon jarbua, Ambassis productus and G. callidus. The species which dominated the fish biomass in the Zotsha were O. mossambicus, L. alata, Valamugil robustus, Valamugil buchanani, M. capensis, M. cephalus and V. cunnesius. Classifying the species captured according to whether they were resident estuarine species, freshwater species, estuarine-dependent marine species and marine species revealed that the first three groups were all well represented in the systems. The only system in which marine species made any significant contribution to the ichthyofauna was the Zotsha. Oreochromis mossambicus was the dominant freshwater species in all three estuaries during this study. Gilchristella aestuaria and Glossogobius callidus were the principal estuarine species in the Mhlanga and the Damba respectively. Both G. aestuaria and G. callidus were the dominant estuarine species captured in the Zotsha. The principal estuarine-dependent marine fishes captured in the Mhlanga were V. cunnesius, Valamugil sp., juvenile mugilids, M. capensis, M. cephalus and L. alata. In the Damba, M. capensis and M. cephalus were the dominant estuarine-dependent marine species and in the Zotsha juvenile mugilids, R. holubi, T. jarbua, A . productus, M. capensis, V. cunnesius, V. robustus, M. cephalus and L. alata predominated. The results of this study indicate that the estuaries are dominated at different periods by different assemblages of fishes. This is linked to the spawning and migration patterns of the various species as well as the hydrological regime of each estuary. During the winter these systems are normally closed with relatively deep waters and high food resource and habitat availability. Freshwater and estuarine species mainly inhabit the upper reaches of the systems while estuarine-dependent marine species mainly occupy the middle and lower reaches and dominate the fish community. When these systems open with the onset of the spring/summer rains, adult and sub-adult estuarine-dependent marine species emigrate to the marine environment and juveniles begin recruiting into the systems. Spring is also the peak breeding period of resident estuarine and freshwater species, resulting in an increase in the contribution of these fishes to the overall population during this period. When closed estuaries open many of them drain and this results in the fishes concentrating in the lower reaches of the system where moderate water depths are present, thus further contributing to an increase in the proportion of freshwater and estuarine species in this region. The breaching of closed estuaries also results in a slump in food resources and habitat availability. Competition and possible increased vulnerability to avian predation (due to the shallow nature of the systems), may contribute to a decrease in the proportion of estuarine and freshwater species in summer. The prolonged spawning and recruitment of 0+ juveniles of estuarine-dependent marine species results in an increase in the proportion of these fishes present in the estuaries during summer. In autumn, these systems normally close, water levels rise and available food resources and habitat increase. This allows the redistribution of freshwater and estuarine species upstream, leaving estuarine-dependent marine species to dominate the middle and lower reaches. Although temporarily open/closed estuaries along the Natal coast may not be as diverse as permanently open estuaries in terms of their ichthyofauna, their importance must not be underestimated since by providing a continuous sequence of sheltered habitats along the coast they may contribute significantly to the viability of estuarine-dependent marine fish stocks.
Keywords: Estuarine ecology -- South Africa -- KwaZulu-Natal; Estuarine animals -- South Africa -- Swartkops River Estuary; Fishes -- South Africa -- KwaZulu-Natal